Multicentric Carpo-Tarsal Osteolysis Syndrome Mimicking Juvenile Idiopathic Arthritis: Two Case Reports and Review of the Literature - Wu, Junfeng; Wang, Li; Xu, Ye; Zhang, Zhiyong; Yan, Xin; An, Yunfei; Zhang, Yu; Tang, Xuemei (Frontiers in Pediatrics, 2021)
Multicentric carpo-tarsal osteolysis syndrome (MCTO) is a rare skeletal disorder commonly caused by MAF bZIP transcription factor B (MAFB) mutation. Clinically, it is characterized by aggressive osteolysis, which mainly affects the carpal tarsal bones, and is frequently associated with progressive nephropathy. Since the painful swelling and motion limitation on the wrists and/or ankles of MCTO mimics those of juvenile idiopathic arthritis (JIA), very often, MCTO is misdiagnosed as JIA. Here, we report two MCTO patients initially diagnosed with JIA but showed no response to treatment: P1, with a medical history of more than 10 years, was presented with a typical triad of arthritis-osteolysis-nephropathy; while P2 showed oligoarthritis. Gene tests were then taken and revealed a novel mutation, p.P63Q, and a previously reported conversion, p.S54L, in the MAFB gene. We also summarized the clinical and genetic features of a cohort containing 49 genetically confirmed MCTO patients. All 51 gene-confirmed MCTO cases (49 identified from the literature plus 2 patients identified herein) developed the disease during childhood. The median delay in diagnosis was 3.83 years (0–35 years). All cases presented bony lesions, and two-thirds had secondary renal lesions (32/48; 3 unknown), half of which (16/32) progressed into renal failure. Almost two-thirds (34/51), 75% (38/51), and 71% (36/51) of patients had no record of eye problems, facial abnormalities, and other manifestations. Most were misdiagnosed as JIA but didn’t respond to treatment. Based on our experience, we suggest that clinicians should comprehensively evaluate the involvement of multiple systems in JIA patients, especially the kidney and eyes. And for JIA patients who underwent more than 3-month treatment with Bio-DMARD, genetic tests are recommended when they show little/no clinical and imaging changes, their high disease activity remains, and their disease activity remission is less than 50%, especially when combined with a triad of arthritis-osteolysis-nephropathy.